Analysis of Transient Stability in Synchronous Generator Using Nyquist Method - Noor Hidayat, Mohammad; Izza, Syarifatul; Ika Putri, Ratna (International Journal of Engineering and Technology, 2018)
There are two factors that must be considered for the power quality analysis of an electrical power system, i.e. frequency and voltage stability. The system that can return to the initial condition or the steady state after a disturbance occurred indicates that the system is stable. This paper aims to detect the transient stability of three generators, which have identical specification of 2.25 MW 6.6 kV and are operated in parallel, based on the frequency performance. In this paper, the stability analysis is determined by using the nyquist method, where the system stability is indicated by the value of the response curve of the system. The analysis results show that the system of three paralleled generators have the value that far from 1 + j0 and the phase margin value and gain margin tend to be minimum. These values indicate that the system is unstable. The system slowly changes into more unstable because the oscillations are getting bigger until the final state. So, it is necessary to change the parameters of each generator that can affect the system stability during synchronization state.Â